Sistem Pendukung Keputusan Penilaian Kinerja Guru Selama Pembelajaran Daring menggunakan Metode Vikor - Sedihati Kayan Lumbangaol; Erna Budhiarti Nababan; Maya Silvi Lydia (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Teacher is a profession that has important role for the progress of education literacy, primarily in this current digitalization era that implements the online learning system. Therefore, the assesment of teacher’s performance during online learning is needed to find the advantages and disadvantages of each teacher, with an aim to get an evaluation that can be utilized to fix or improve the teacher’s performance. This study proposes a decision support system that applies the Vikor method as a solution to get the result of teacher’s performance assessment during online learning and make it easier for the decision makers. By using 4 research criteria and 5 alternatives, this research shows that A5 on behalf of Kayan Marbun with a value of 0.5025 is chosen as the teacher with the best performance.